THE EFFECT OF CUSTOMER EXPERIENCE AND SERVICESCAPE ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION AS A VARIABLE INTERVERNING ON ME & COFFEE WORKS WAHID HASYIM MEDAN - Rindi Sharifa; Endang Sulistya Rini; Amlys Syahputra Silalahi (CV. Radja Publika, 2023)
This study aims to determine and analyze the effect of customer experience and servicescape on customer loyalty through customer satisfaction as an intervening variable in me & coffee works by Wahid Hasyim Medan. The population in this study is the people of Medan City with 6 sub-districts including the sub-district of Me & Coffee Works customers who have visited at least 2 times with an unknown number. The sampling technique in this study was non-probability sampling as many as 85 respondents. The data analysis method uses Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results of the study show that customer experience has an effect on customer loyalty. Servicescape influences customer loyalty. Customer experience influences customer satisfaction. Servicescape influences customer satisfaction. Customer satisfaction affects customer loyalty. Customer experience influences customer loyalty through customer satisfaction as an intervening variable. Servicescape influences customer loyalty through customer satisfaction as an intervening variable.